2020
DOI: 10.3389/fcvm.2020.597374
|View full text |Cite
|
Sign up to set email alerts
|

Ras Pathways on Prox1 and Lymphangiogenesis: Insights for Therapeutics

Abstract: Over the past couple of decades, lymphatics research has accelerated and gained a much-needed recognition in pathophysiology. As the lymphatic system plays heavy roles in interstitial fluid drainage, immune surveillance and lipid absorption, the ablation or excessive growth of this vasculature could be associated with many complications, from lymphedema to metastasis. Despite their growing importance in cancer, few anti-lymphangiogenic therapies exist today, as they have yet to pass phase 3 clinical trials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 178 publications
(189 reference statements)
3
31
0
Order By: Relevance
“…Lymphangiogenesis is regulated by the VEGFC‐VEGFR3 axis and the ERK pathway. 31 In the present study, we found that Ang II‐induced hypertension inhibited lymphangiogenesis and down‐regulate the expression of lymphatic markers in mice hearts and decrease VEGFC in their serum, and SIRT3‐KO further suppressed these processes. In vitro, Ang II reduced function, expression of VEGFR3 and phosphorylation of ERK in LECs, which could be further down‐regulated by inhibition of SIRT3, but up‐regulated after SIRT3 overexpression, suggesting VEGFC‐VEGFR3 axis, and the ERK pathway may be associated with SIRT3‐regulated lymphangiogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Lymphangiogenesis is regulated by the VEGFC‐VEGFR3 axis and the ERK pathway. 31 In the present study, we found that Ang II‐induced hypertension inhibited lymphangiogenesis and down‐regulate the expression of lymphatic markers in mice hearts and decrease VEGFC in their serum, and SIRT3‐KO further suppressed these processes. In vitro, Ang II reduced function, expression of VEGFR3 and phosphorylation of ERK in LECs, which could be further down‐regulated by inhibition of SIRT3, but up‐regulated after SIRT3 overexpression, suggesting VEGFC‐VEGFR3 axis, and the ERK pathway may be associated with SIRT3‐regulated lymphangiogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…While VEGF, a ligand of VEGFR2 is an essential factor for blood vessel development, VEGF-C is the major ligand that activates VEGFR3 for lymphatic vascular development ( 1 , 49 ). VEGF-C/VEGFR3 interaction activates PI3K-AKT and PKC-ERK pathways to regulate LECs proliferation, survival, and migration ( 50 ). It has been reported that VEGF-C treatment increased phospho-LATS1 and facilitated cytoplasmic YAP whereas VEGFR3 knockdown promoted nuclear localization of YAP, thereby suggesting that VEGF-C activates the Hippo signaling to repress YAP/TAZ in hLECs ( 45 ).…”
Section: Upstream Signals Regulating Hippo-yap/taz Pathway In Lecsmentioning
confidence: 99%
“…Prox-1 is a major transcription factor of lymphatic development and mutations of the PROX1 gene have been reported in lymphedema patients ( Ricci et al, 2020 ). Studies on the effects of PROX1 knockout in mouse models induced lymphatic vasculature dysfunction ( Srinivasan and Oliver, 2011 ; Bui and Hong, 2020 ). Studies on the role of miRNAs in lymphedema-related inflammation are still lacking and some of the reported miRNAs have yet to be validated in human samples, using different diseases and models.…”
Section: Mirnas and Inflammation-induced Lymphangiogenesismentioning
confidence: 99%